Clinical Efficiency of Vasopressin or Its Analogs in Comparison With Catecholamines Alone on Patients With Septic Shock: A Systematic Review and Meta-Analysis - Yao, Ren-qi; Xia, De-meng; Wang, Li-xue; Wu, Guo-sheng; Zhu, Yi-bing; Zhao, Hong-qiang; Liu, Qi; Xia, Zhao-fan; Ren, Chao; Yao, Yong-ming (Frontiers in Pharmacology, 2020)
Background: Vasopressin is an efficient remedy for septic shock patients as a pivotal complement of fluid resuscitation. The aim of current systematic review and meta-analysis is to compare the clinical efficiency of vasopressin or its analogues with sole catecholamines on patients with septic shock. Methods: A systematic search of Cochrane Library, EMBASE, and PubMed online databases was performed up to 30 Oct 2019 to identify randomized controlled trials comparing use of vasopressin or its analogues (e.g. terlipressin, selepressin) with administration of catecholamines alone. Results: We included 23 RCTs with 4225 patients in the current study. Compared with solely use of catecholamines, administration of vasopressin or its analogues were associated with reduced 28-day or 30-day mortality among patients with septic shock (RR=0.94 [95% CI, 0.87-1.01], P=0.08, I2 = 0%). The result of primary endpoint remained unchanged after conducting sensitivity analysis. Despite a significantly higher risk of digital ischemia in patients receiving vasopressin or its analogues (RR=2.65 [95% CI, 1.26-5.56], P < 0.01, I2 = 48%), there was no statistical significance in the pooled estimate for other secondary outcomes, including total adverse events, arrhythmia, AMI and cardiac arrest, acute mesenteric ischemia, ICU/hospital length of stay, and mechanical ventilation (MV) duration. Conclusions: The administration of vasopressin or its analogues was not associated with a reduced 28-day or 30-day mortality among patients with septic shock, while an increased incidence of digital ischemia should be noted in patients receiving agonists for vasopressin receptors.